2018
DOI: 10.13152/ijrvet.5.4.4
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Learners with Disabilities in Mainstream Vocational Training in Nepal

Abstract: Context: This article explores the lived experiences of learners with disabilities who were attending short-term skills-based training programs in Nepal. The research questions addressed were how the learners with disabilities had been experiencing learning with their peers without disabilities and whether the vocational training was inclusive from the perspectives of learners with disabilities. Approach: Based on a phenomenological design, eight learners with disabilities were purposively selected. In-depth i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Young people's experiences of intervention quality included three themes, curriculum and content, instruction and instructor, and management and administration. The majority of participants in 13 studies that contained evidence of curriculum and content reported negative experiences (Apunda et al 2017;Bhurtel 2016;Botea et al 2015 Young people's learning experiences were also affected by the quality of instruction and instructors (Adhikari 2018;Apunda et al 2017;Bhurtel 2016;Ling 2015;Sedighi et al 2015;Veazey 2014). While few participants considered their instructors competent (Apunda et al 2017), others lamented the textbook-based authoritarian pedagogy that discouraged them to develop intellectual curiosity and critical thinking ability (Veazey 2014).…”
Section: Intervention Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…Young people's experiences of intervention quality included three themes, curriculum and content, instruction and instructor, and management and administration. The majority of participants in 13 studies that contained evidence of curriculum and content reported negative experiences (Apunda et al 2017;Bhurtel 2016;Botea et al 2015 Young people's learning experiences were also affected by the quality of instruction and instructors (Adhikari 2018;Apunda et al 2017;Bhurtel 2016;Ling 2015;Sedighi et al 2015;Veazey 2014). While few participants considered their instructors competent (Apunda et al 2017), others lamented the textbook-based authoritarian pedagogy that discouraged them to develop intellectual curiosity and critical thinking ability (Veazey 2014).…”
Section: Intervention Qualitymentioning
confidence: 99%
“…Furthermore, some instructors failed to address the learning needs of the minority students. For instance, learners with disabilities in mainstream vocational centers reported that students with physical disabilities could understand the subject matter but had difficulty in performing the tasks, but those with visual and hearing impairments could not understand the lecture at all (Adhikari 2018).…”
Section: Intervention Qualitymentioning
confidence: 99%
See 3 more Smart Citations